Morphological changes of different castes of the subterranean termites (Odontotermes proformosanus) in fungus combs of termitophiles (The Journal of Plant Protection Sciences, 2021)
Termitidae is the largest family of termites. The workers of the subfamily Macrotermitinae have the extra-ordinary  phenomena of making fungus combs inside the termitophiles. Considering the consistency of fungus-bed in the  termitophiles, an attempt has been made to observe the morphological changes of nymphs while they stayed within the  fungus comb. Biological attributes indicated that Odontotermes proformosanus are polymorphic in nature and have  exopterygote post-metamorphic development. During the period of study, eggs and nymphs were collected in different  seasons from the fungus combs of termite mounds. Eggs of O. proformosanus were found profusely in fungus comb in  the months of March, May, September and October of 2006 to 2008 Average lengths and standard deviation (mean±SD)  of the eggs were (0.66 ± 0.09), width (0.04 ± 0.07) mm and egg shape ratio is 0.53. Eggs were mostly of broad type.  st th st Distinct quiescent period was also observed. Morphological changes completed within 1 to 5 stages. In the 1 stage,  th total length ranged from 0.8-1.5 mm. Terminal form of workers and soldiers were attained at the 5 stage (4.1- 4.5 mm in  body length). During the period of observation, it was found that total length of the nymph, head length and head capsule  width are significantly correlated at 0.01 level in their five different development stages.
Keywords: Fungus comb; Odontotermes proformosanus; morphological changes; nymphs; termitophiles